Moderasi Beragama yang Kosmopolit (Mencegah Konflik dalam Masyarakat Sodong yang Harmoni) - Rufi’ah, Rufi’ah; Wijaya, Aksin; Hasaniy, Nur Rif’ah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article focuses on the theme of inter-religious relations in Indonesia with interrelated sub-topics: the history of the struggle of thought in Islam, the concept of religious moderation, and looking at religious life in a hamlet that has been used as a hamlet of religious tolerance in Ponorogo, namely the hamlet of Sodong. The history of thought and religious moderation are used to discuss the above issues. The history of thought is intended to trace the struggle of thought in history, while religious moderation is used as an analytical tool and solution offering to prevent the emergence of potential conflicts in the Sodong Community, Ponorogo. Viewed from the perspective of the history of thought, religious moderation has actually been developing for a long time, namely since the early period of the presence of Islam, and its presence has always been a response to radical thoughts and attitudes in religion. The religious moderation that I think is appropriate to use in Indonesia is religious moderation that is dialogical with reality, because Islam basically has a theoretical, dialogical and practical character. With the basic character of Islam, we can see reality in an appreciative, critical and productive way. We can appreciate the phenomenon of tolerant religiosity, of course without reducing critical attitudes and new solutions in overcoming potential conflicts in the name of religion, such as in Sodong Ponorogo.